Proceedings of the 2020 Conference on Empirical Methods in Natural Language Processing (EMNLP) 2020
DOI: 10.18653/v1/2020.emnlp-main.676
|View full text |Cite
|
Sign up to set email alerts
|

Deep Attentive Learning for Stock Movement Prediction From Social Media Text and Company Correlations

Abstract: In the financial domain, risk modeling and profit generation heavily rely on the sophisticated and intricate stock movement prediction task. Stock forecasting is complex, given the stochastic dynamics and non-stationary behavior of the market. Stock movements are influenced by varied factors beyond the conventionally studied historical prices, such as social media and correlations among stocks. The rising ubiquity of online content and knowledge mandates an exploration of models that factor in such multimodal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 60 publications
0
59
0
Order By: Relevance
“…Bias in Finance Public financial data is impacting virtually every aspect of investment decision making (Perić et al, 2016;Brynjolfsson et al, 2011). Prior research shows that NLP methods leveraging social media (Sawhney et al, 2020a), news (Du and Tanaka-Ishii, 2020), and earning calls (Wang and Hua, 2014) can accurately forecast financial risk. Companies and investors use statistical and neural models on multimodal financial data to forecast volatility (Cornett and Saunders, 2003;Trippi and Turban, 1992) and minimize risk.…”
Section: Background: Why Study Bias?mentioning
confidence: 99%
“…Bias in Finance Public financial data is impacting virtually every aspect of investment decision making (Perić et al, 2016;Brynjolfsson et al, 2011). Prior research shows that NLP methods leveraging social media (Sawhney et al, 2020a), news (Du and Tanaka-Ishii, 2020), and earning calls (Wang and Hua, 2014) can accurately forecast financial risk. Companies and investors use statistical and neural models on multimodal financial data to forecast volatility (Cornett and Saunders, 2003;Trippi and Turban, 1992) and minimize risk.…”
Section: Background: Why Study Bias?mentioning
confidence: 99%
“…For this study, we derive inspiration from Hu et al (2017); Sawhney et al (2020Sawhney et al ( , 2021 to design the policy network. However, it is important to note that PROFIT is compatible with any general deep network that is capable of handling time-series of textual data.…”
Section: Trading Policy Networkmentioning
confidence: 99%
“…• MAN-SF (text only): BERT based hierarchical encoder for financial text using hierarchical temporal attention (Sawhney et al, 2020).…”
Section: Classification (Clf)mentioning
confidence: 99%
“…Advances in NLP have been utilized in many approaches to show financial information significantly improving performance in forecasting tasks like volatility and stock price prediction (Wang et al, 2013;Ding et al, 2015;Mittermayer and Knolmayer, 2007). Research has also shown that social media affects the stock market (Bollen et al, 2010;Oliveira et al, 2017;Sawhney et al, 2020a). Machine learning methods using simple bag-of-words features to represent the financial documents used in previous research (Kogan et al, 2009;Rekabsaz et al, 2017) largely ignore the inter-dependencies between the sentences.…”
Section: Related Workmentioning
confidence: 99%